2021
DOI: 10.1155/2021/2672772
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Duct Carcinoma: Case Reports and Brief Review of the Literature

Abstract: Salivary duct carcinoma (SDC) is an uncommon and highly aggressive tumor associated with high morbidity and mortality. According to the World Health Organization, it is an extremely rare malignancy with an estimated incidence of 1-1.2 in 1,000,000 patients. Standard treatment for SDC is wide surgical resection along with lymph node dissection followed by adjuvant radiation therapy. The role of adjuvant chemotherapy is not known. In this report, we present three cases of SDC. A 71-year-old female with T1N0M0 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Chemotherapy, commonly anti-androgen rather than cytotoxic, is considered for patients with distant metastases or palliatively (Kantamani et al, 2021;Nakaguro, et al, 2018). Several studies reported use of androgen deprivation therapy with androgen receptor inhibitors as monotherapy or in combination with gonadotropin hormone-releasing hormone, luteinizing hormone-releasing agonists or HER-2 targeted therapy and a taxane (Eveson, 2006; Matsumiya-Matsumoto, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy, commonly anti-androgen rather than cytotoxic, is considered for patients with distant metastases or palliatively (Kantamani et al, 2021;Nakaguro, et al, 2018). Several studies reported use of androgen deprivation therapy with androgen receptor inhibitors as monotherapy or in combination with gonadotropin hormone-releasing hormone, luteinizing hormone-releasing agonists or HER-2 targeted therapy and a taxane (Eveson, 2006; Matsumiya-Matsumoto, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%